APLIKASI ABSENSI JEMAAT BERBASIS ANDROID PADA GEREJA KRISTEN INDONESIA GADING SERPONG - Michael; Edy (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
Abstract : It will be difficult for the congregation to attend services without having to carry a church card at all times. In order to tackle congregational issues with attendance, this research was done in order to design and develop an Android-based church attendance application. This system was designed and developed using the RAD (Rapid Application Development) methodology. The author created the program "Android-Based Attendance Application for the Indonesian Christian Church Gading Serpong" based on an examination of the attendance procedure for the congregation that meets at GKI Gading Serpong. Making this application is in line with the research's goals to reduce the need for actual church cards, solve the issue of lost or damaged church cards, make it simpler for the congregation to view the schedule of events, and assist in reminding the congregation about future events. The number of Paths with the results of calculations using the formula is produced using whitebox testing, and the results are the same. This can be interpreted that there is no error code contained in the program. The results of the interviews were taken from 20 people who filled out the questionnaire. From these respondents, 93% answered yes or agreed that this application could be used properly. Based on the results of these respondents, that respondents can feel the benefits of this application in minimizing the loss or damage of church cards and getting information they can use this application to carry out attendance, view activity schedules, and receive notifications about activities.